Improving The Students’ Reading Comprehension Through Word Attack Strategy - Harahap, Fitri (Journal of Applied Linguistics, 2024)
This study was conducted to find out the improving the researcher used experimental research. The sample of this research consisted of 60 students at the fourth-semester nutrition Department Faculty of Public Health Institut Kesehatan Medistra Lubuk Pakam 2023/2024. The population data from one class were gathered through the use of the cluster sampling approach. The pretest was used to gauge the students' beginning reading proficiency. Following the application of the word attack strategy treatment, the posttest was administered. As a research tool, multiple-choice tests were used to gather the data. The statistics used in data analysis indicated that the t-test calculation's result, which is the observed value (8,26), is greater than the t-table value (1.67155). It denotes the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). The word attack strategy was found to be more successful in improving reading comprehension. To lecturers and teachers, the writer advises all lecturers and teachers especially those who teach English to use the word attack strategy. For students to be more engaged and capable of critical thought toward both teachers and other students. Keywords: Word Attack Strategy; Reading Comprehension